2023
DOI: 10.1186/s13099-023-00542-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Virulence and β-lactamase resistance genes of non-typhoidal Salmonella isolates from human and animal origin in Egypt "one health concern"

Abstract: Background Non-typhoidal Salmonella (NTS) is a major foodborne zoonotic pathogen worldwide. In the current study, Various NTS strains were isolated from (cows, milk and dairy products in addition to humans) in New Valley and Assiut Governorate, Egypt. NTS were firstly serotyped and tested by antibiotic sensitivity test. Secondly, some virulence genes and Antibiotic resistance genes have been identified by using PCR. Finally, Phylogenesis was performed depending on the invA gene, for two S. typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…To address this critical knowledge gap, we investigated Salmonella strains for the possible presence of genes encoding for β-lactamases. The majority of the Salmonella isolates in the current study and surveillance studies of Salmonella in dairy products [17,18,26], camel meat [38], retailed beef and chicken meat [39], and among food handlers and human patients [26] from Egypt were XDR or MDR, which have been confirmed to be positive for at least one or more NSBL (bla OXA-1 + bla OXA-2 ) genes, as well as plasmid-and chromosome-encoded ESBL (bla CTX-M + bla TEM-1 ) genes and AmpC BL (bla CMY-1 + bla CMY-2 ) resistant genes. Similarly, bla OXA-1 , bla CTX-M , and bla TEM-1 were the most frequently identified β-lactams resistance genes of E. coli and Shigella species recovered from raw milk and dairy products marketed in Egypt [40,41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To address this critical knowledge gap, we investigated Salmonella strains for the possible presence of genes encoding for β-lactamases. The majority of the Salmonella isolates in the current study and surveillance studies of Salmonella in dairy products [17,18,26], camel meat [38], retailed beef and chicken meat [39], and among food handlers and human patients [26] from Egypt were XDR or MDR, which have been confirmed to be positive for at least one or more NSBL (bla OXA-1 + bla OXA-2 ) genes, as well as plasmid-and chromosome-encoded ESBL (bla CTX-M + bla TEM-1 ) genes and AmpC BL (bla CMY-1 + bla CMY-2 ) resistant genes. Similarly, bla OXA-1 , bla CTX-M , and bla TEM-1 were the most frequently identified β-lactams resistance genes of E. coli and Shigella species recovered from raw milk and dairy products marketed in Egypt [40,41].…”
Section: Discussionmentioning
confidence: 95%
“…Tasmin et al [25] reported that Salmonella strains retrieved from infected animals and birds exhibit a higher incidence of the plasmid-associated spvC gene. Recent investigations from Egypt [23,26] and Bangladesh [27] highlighted that the occurrence rate of the spvC gene is limited across S. Enteritidis, S. Typhimurium, and S. Infantis isolated from retailed foods. In the current study, the spvC gene was found to be restricted to all S. Typhimurium serotypes, and it is consistent with the findings of Zou et al [28] and Elzhraa et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the spv operon (namely spvB , spvC , and spvR ) and the genes inv A, hil A, fim A, and stn are usually associated with severe infections in non-typhoidal Salmonella [ 53 , 54 , 55 ]. In the current study, 100% of strains carried the genes invA and hilA , 92.2% harbored the fimA gene, and 90.2% carried the spvB gene.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the spv operon (namely spvB, spvC, and spvR) and the genes invA, hilA, fimA, and stn are usually associated with severe infections in non-typhoidal Salmonella [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical improvement occurred in our case before discharge from hospital, this was unlikely to be a result of clindamycin administration, as S Typhimurium isolates are uniformly resistant to clindamycin. 17 …”
Section: Discussionmentioning
confidence: 99%